Soil washing contaminated with heavy metals by using bacterial bioemulsifier at laboratory scale - Castro, María Fernanda (2013)
Heavy metal cannot be degradable into innocuous products and they tend to be strongly absorbed on the matrix of soils and sediments. These characteristics limit their solubilization and subsequent removal. An effective method to increase the metal-desorption of soil and sediments involves washing technologies assisted with surface active compounds as such bioemulsifiers. However, there is little information found in the literature regarding bacterial bioemulsfiers used for this purpose. In previous studies, it have being demonstrated the ability to produce bioemulsifier by an actinobacterium, Amycolatopsis tucumanensis DSM 45259, using different carbon and nitrogen sources. Also it was showed that both production and hence functional properties of bioemulsifier is associated mainly to carbon sources used for biosynthesis. Following these studies, the objective of the present work was to study the applicability of bioemulsifiers produced by A. tucumanensis DSM 45259 from different carbon a nitrogen sources, as washing agents in environmental remediation technologies, as well as to determine whether Cu(II) or Cr(VI) presence affecting the bioemuslfier production. To achieve this, soil samples were artificially contaminated with Cu(II) or Cr(VI) added as CuSO 4 .5H 2 O and K 2 Cr 2 O 7 , respectively, at final concentration of 200 mg kg −1 of soil. Washing experiments were performed using 2.0 g of contaminated soil in flasks. Soils were washed with 10 ml of aqueous solutions of the partially purified bioemulsifiers, using deionized water as control. Emulsification index of each bioemulsifier solution was previously adjusted to 60%. The washing procedures were performed by shaking at 30 ºC between 12 to 24 h. Soil samples were centrifuged at 10,000g and the concentration of Cu(II) and Cr(VI) in supernatants were analyzed by atomic absorption spectrometry and Cr(VI) concentration was measured using a colorimetric method. Under these assayed conditions, no significant Cu(II) removal could be detected after 12 h of washed either with H 2 Od or bioemulsifier solutions. However, A. tucumanensis bioemulsifiers seemed to be effective for Cr(VI) recovery, whose removal from soil increased 2 fold while compared to H 2 Od. Cr removed in the washing experiments remains in its hexavalent state. The increase of the in the washing time, did not improve the Cu(II) and Cr(VI) removal. Analysing the different effects of carbon and nitrogen sources and metal type, the last one was the most relevant variable that influence on the washing efficiency. In relation to the production of bioemulsifier by A. tucumanensis DSM 45259 in the presence of metals, the results showed that the assayed concentrations of Cu(II) and Cr(VI) (10, 20 and 30 ppm) in the culture media did not affect the bioemulsifier production. These are the first advances conducted in our research group focused on the direct application of microbial products in heavy metal remediation strategies.